Hubungan Principal Agent Kontrak Zakat Pada Kelembagaan Zakat Indonesia dan Malaysia - Syawaluddin S (Media Syari'ah, 2017)
This paper is a comparative study in two countries, Malaysia and Indonesia concer ning the principal agent relationship where the contract zakat zakat in terms of urgency,both in terms of worship and socio-economic demands good management and professional zakat. Indeed, the management of Zakat since the time of the Prophet until the fall of the Islamic caliphate is the responsibility of the government. But lately zakat management models in some Muslim countries be varied, are managed by countries like Yemen and Malaysia. There is also the countries that make charitable contributions through private management including Kuwait, Bangladesh and South Africa. Interestingly, as one of the Muslim countries, zakat management in Indonesia is carried out by the government and also the private sector simultaneously.